Model Pembelajaran Katekisasi bagi Anak Penyandang Autisme: Tinjauan PAK terhadap Proses Katekisasi bagi Anak Penyandang Autisme di Jemaat HKBP Palangkaraya - Marpaung, Flowrent Natalia; Rantung, Djoys; Naibaho, Lamhot (Lembaga Yasin AlSys, 2023)
As Christians, the church is a place forour knowledge and spirituality to develop. Therefore, faith development in the church is a good step to be taught from children to adults. One of the Christian activities that can grow His faith and love for God's Word is to carry out sidi. But before carrying out sidi, first to do catechism. Catechism is a part that cannot be separated, especially for adults. But basically, the learning model for catechism is something we need to pay attention to so that children who grow up in faith are interested and can see God's gifts. The learning model is a challenge to the church so that it can innovate for maximum teaching. In addition to the learning model for catechism children, especially for children who have autism, it can be a new thing for the church. Because the majority of churches still do not realize that children with autism need special attention in the catechism learning model.